Educational Psychology in the Context of Gifted Students: Addressing the Challenges and Opportunities in the Development of Academic Potential - Amahoru, Archristhea; Saepuloh, Aep; Mahmudah, Mahmudah; Judijanto, Loso; Fauzi, Muhammad Sukron (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
This study aims to analyze the challenges and opportunities in the development of the academic potential of gifted students within the context of educational psychology. Gifted students often face challenges related to the mismatch between the existing curriculum and their intellectual abilities, which can lead to boredom, decreased motivation, and social-emotional difficulties. On the other hand, there are opportunities to address these challenges through differentiated teaching approaches, the use of educational technology, and enhanced social support. This research is a literature study aimed at reviewing and analyzing various literature related to educational psychology in the context of gifted students. The study uses a qualitative approach by collecting data and information from various secondary sources such as books, academic journals, articles, research reports, and other related documents. The study aims to gain a deep understanding of the challenges and opportunities in the development of the academic potential of gifted students, as well as the role of educational psychology in supporting them. The findings underline the importance of personalized teaching and strong social and emotional support in fostering the development of gifted students. This research provides insights for educators and policymakers in designing educational programs that can optimize the potential of gifted students across various educational settings.